PERLINDUNGAN HUKUM TERHADAP PEKERJA ANAK DI INDONESIA DALAM PERSPEKTIF INTERNATIONAL LABOUR ORGANIZATION CONVENTION - Sari, Isna Kartika; Deliana, Evi; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In order to ensure the rights of children and reduce the adverse effects of child labor, a number of rules have been set up to provide protection to child labor such as the ILO Convention concerning The Prohibition and Immediate Action for the Elimination of the Worst Forms of Child Labor and Minimum Age for Admission to Employment. However, various forms of action that resulted in non-fulfillment of rights in children is still often occur. The purpose of this thesis, namely; First, to provide comprehension of the legal protection of child laborers in Indonesia in the perspective of the ILO Convention, Second, to provide comprehension of the barriers to legal protection of child labor in Indonesia.The type of research used in this thesis is normative legal research. The author conducts research on legal principles that start from certain legal areas. Where the authors are guided by the provisions applicable as legal protection against child labor in Indonesia.This thesis discussed about; First, from the existing data can be seen that Indonesia has not been able to implement the agreement with the maximum in accordance with the principle of pacta sunt servanda. Implementation of legal protection against child labor has not matched expectations and reality. In addition, the ILO Convention has not fully fulfilled the rights of children, particularly in children who is working in the informal sector. Second, the barriers to legal protection of child labor in Indonesia are complex and related to various aspects of life, consisting of factors, improper implementation of the provisions, and socio-cultural factors. The suggestion of this tesis are; First, the government has to implement and follow up the provisions set by the ILO Convention because the implementation still has not achieved the goal of the rule. Currently, legislation focuses on the protection of working children, not specifically aimed at eliminating the existence of child labor. So the government should make a comprehensive regulation to eliminate the existence of child labor. Second, the active role of various parties responsible and responsible for the implementation of legal protection of child labor is required. The relevant agencies must carry out their respective roles and responsibilities in order to prevent and cope with child labor. The community should be given a comprehension of the importance of child rights protection and fulfillment. More efforts must be done continuously, sustainably, and unified by all parties together.Keywords: Legal Protection - Child Labor - ILO Conventions